LATTICE UNIVERSALITY OF LOCALLY FINITE \(p\)-GROUPS - Vladimir B. Repnitskiǐ (Ural Mathematical Journal)
For an arbitrary prime \(p\), we prove that every algebraic lattice is isomorphic to a complete sublattice in the subgroup lattice of a suitable locally finite \(p\)-group. In particular, every lattice is embeddable in the subgroup lattice of a locally finite \(p\)-group.